Deep Breathing Relaxation Therapy for the Implementation of Acute-Pain in Post-ORIF of Patella Sinistra Fractures Patients - Silpiyani Silpiyani; Dwi Novitasari (Genius Journal, 2023)
Objective: The study aims to find out whether the intensity of pain decreases after the application of non-pharmacological techniques of deep breathing relaxation. Method: Method used in descriptive case study with approach to nursing process. Population in this study of post-ORIF of fractures patella sinistra patients in Wijayakusuma ward Kardinah Hospital, Tegal City, who have experienced acute pain nursing problems. Data collection in this study was carried out through interviews, observations, and physical examinations. The analysis of data in this study is performed in a descriptive narrative manner using PDCA for patient development, the presentation of data is described descriptively to know the results obtained during conducting a case study. Result: The results of the study showed that the respondent’s pain intensity decreased from a 5 pain score to a 3 pain score after non-pharmacological respiratory relaxation therapy was administered. Conclusion: Deep breathing relaxation therapy can be used to reduce the intensity of pain in post-orif fractural respondents. It is hoped that this non-pharmacological breathing relaxation technique can be used by health care professionals, especially nurses, as a way to reduce the scale of respondent pain.